2007
DOI: 10.1103/physreve.75.061703
|View full text |Cite
|
Sign up to set email alerts
|

Orientational relaxation in a discotic liquid crystal

Abstract: We investigate orientational relaxation of a model discotic liquid crystal, consisting of disclike molecules, by molecular dynamics simulations along two isobars starting from the high temperature isotropic phase. The two isobars have been so chosen that (a) the phase sequence isotropic- (I-) nematic- (N-) columnar (C) appears upon cooling along one of them and (b) the sequence isotropic- (I-) columnar- (C) along the other. While the orientational relaxation in the isotropic phase near the I-N phase transition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Bagchi and coworkers showed with the Gay-Berne model that isotropic-nematic (I-N, weakly rstorder) and isotropic-columnar (I-C, strongly rst-order) phase transitions exhibit distinct orientational relaxation dynamics. 52,53 Specically, the authors observed a power-law decay of the OKE at short-to-intermediate timescales for the I-N phase transition, being absent in the I-C phase transition. Near the I-N phase transition, mesogen uids exhibit typical signatures of glass-forming liquids, including dynamical heterogeneity, non-Arrhenius temperature dependence of the orientational relaxation time, and non-exponential relaxation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Bagchi and coworkers showed with the Gay-Berne model that isotropic-nematic (I-N, weakly rstorder) and isotropic-columnar (I-C, strongly rst-order) phase transitions exhibit distinct orientational relaxation dynamics. 52,53 Specically, the authors observed a power-law decay of the OKE at short-to-intermediate timescales for the I-N phase transition, being absent in the I-C phase transition. Near the I-N phase transition, mesogen uids exhibit typical signatures of glass-forming liquids, including dynamical heterogeneity, non-Arrhenius temperature dependence of the orientational relaxation time, and non-exponential relaxation.…”
Section: Introductionmentioning
confidence: 97%
“…54 The Gay-Berne model has also been shown to capture a pretransitional effect, 55,56 where local pseudonematic domains strongly inuence spatial correlations of discogens in the isotropic phase, leading to an increasing correlation length scale as the I-N phase transition is approached. [52][53][54] Caprion and coworkers, in studying different aspect ratios, elucidated differences in the diffusivity of discogens in isotropic, nematic, and columnar phases by mapping timescales from their Monte Carlo study. 28 A similar time-mapping scheme was carried out by Patti and coworkers to characterize the long-time relaxation dynamics of oblate hard spherocylinders in columnar mesophases.…”
Section: Introductionmentioning
confidence: 99%
“…When a different isobar was chosen at a lower pressure for the discotic system, a direct transition from the isotropic phase to the columnar phase was observed. In this case, decay of neither the single-particle second-rank OTCF nor the OKE signal showed any power law regime . We note that the isotropic−columnar (I−C) transition is strongly first-order in nature, as reflected in the present case with a much larger change in the density corresponding to the I−C transition as compared to the I−N transition.…”
Section: Results On Analogous Dynamicsmentioning
confidence: 50%
“…As the I-N phase boundary is crossed upon cooling, the advent of two power law decay regimes separated by an intervening plateau at shortto-intermediate times imparts a step-like feature to the temporal behaviour of the second rank OTCF. Such power law relaxation near I-N phase boundary was an area of great interest in the recent past [11][12][13][14][15][16] and it has been investigated that the scenario is not a unique property of the model we have studied; it is a rather universal phenomenon of second rank OTCF. 17 Such a feature bears remarkable similarity to what is observed for supercooled liquids as the glass transition is approached from the above.…”
Section: Single Particle Orientational Dynamicsmentioning
confidence: 99%